A theory-based intervention delivered by an online social media platform to promote oral health among Iranian adolescents: a cluster randomized controlled trial. Issue 4 (2nd April 2020) - Scheerman, Janneke Francisca Maria; Hamilton, Kyra; Sharif, Mohammad Owaise; Lindmark, Ulrika; Pakpour, Amir H.
Abstract: Objective: Based on the Health Action Process Approach, we tested the efficacy of a theory-based program using an online social media platform (Telegram) to promote good oral hygiene behaviour among Iranian adolescents. Design: A three-arm randomized-controlled trial design was used, consisting of an adolescent only intervention group (A group; n  = 253), an adolescent and mother intervention group (A + M group; n  = 260), and a control group ( n  = 278). Main outcome measures: Psychosocial variables, toothbrushing behaviour, Visual Plaque Index, and Community Periodontal Index. Results: Increases in adolescent toothbrushing at the one- and six-month follow-ups in both intervention groups compared to the control group were observed. Adolescents in the A + M group showed significant greater improvements in their toothbrushing behaviour, Visual Plaque Index, and Community Periodontal Index scores than adolescents in the A group. Improvements to toothbrushing social cognitions were also observed. Conclusions : Current results support the use of the theory-based program delivered by Telegram in improving good oral hygiene behaviour and oral health outcomes among Iranian adolescents. Involving mothers in an intervention can confer additional benefits for adolescent oral health.